2020
DOI: 10.1155/2020/4534272
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Serological Biomarkers of sICAM-1, IL-1β, MIF, and su-PAR with 3-Month Mortality in Acute Exacerbation of Idiopathic Pulmonary Fibrosis

Abstract: Objective. To investigate prognostic values of serum biomarkers of soluble intercellular adhesion molecule 1 (sICAM-1), macrophage migration inhibitor factor (MIF), interleukin 1β (IL-1β), and soluble urokinase plasminogen activator receptor (su-PAR) in patients with acute exacerbation of idiopathic pulmonary fibrosis (AE-IPF). Methods. From August 2017 to November 2019, 122 consecutive IPF patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Brain MRI has become a common imaging modality at present, and it applies radiofrequency pulses of specific frequency to the human body in the static magnetic field, so that the hydrogen protons in the human body are stimulated and then cause magnetic resonance; after stopping the pulse, the protons produce MR signal during relaxation, and with the continuous promotion of MRI imaging sequence and image, brain MRI provides a good basis for the diagnosis of brain lesions [17]. Moreover, MRI is effective in detecting cerebral small vessel injury because it is noninvasive and easy to operate.…”
Section: Discussionmentioning
confidence: 99%
“…Brain MRI has become a common imaging modality at present, and it applies radiofrequency pulses of specific frequency to the human body in the static magnetic field, so that the hydrogen protons in the human body are stimulated and then cause magnetic resonance; after stopping the pulse, the protons produce MR signal during relaxation, and with the continuous promotion of MRI imaging sequence and image, brain MRI provides a good basis for the diagnosis of brain lesions [17]. Moreover, MRI is effective in detecting cerebral small vessel injury because it is noninvasive and easy to operate.…”
Section: Discussionmentioning
confidence: 99%
“…Several prognostic staging systems for IPF have been established by clinical and physiologic variables (2)(3)(4)(5). Biomarkers in peripheral blood are also evaluated as a tool for prognosis (6)(7)(8). A recent study also revealed the role of genetic variability in the survival of IPF (9).…”
Section: Introductionmentioning
confidence: 99%
“…Interleukin −1β is a key pro-inflammatory cytokine, which plays an important role in cell proliferation, differentiation and apoptosis, and is also a fibrogenic factor. Recent studies have found that IL-1β is higher in acute exacerbation of idiopathic pulmonary fibrosis than in stable period, and it is an independent risk factor for death within 3 months [42]. Tumor necrosis factor-α is a multi-directional pro-inflammatory cytokine secreted by many inflammatory cells.…”
Section: Discussionmentioning
confidence: 99%